2007
DOI: 10.2337/db06-0918
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Diabetes Onset During Metformin Versus Placebo Therapy in the Diabetes Prevention Program

Abstract: on behalf of the DPP Research GroupIn the Diabetes Prevention Program, treatment of subjects with impaired glucose tolerance with metformin >3.2 years reduced the risk of developing type 2 diabetes by 30% compared with placebo. This study describes the mechanisms of this effect. In proportional hazards regression models with 2,155 subjects, changes in weight, the insulinogenic index (IGR), fasting insulin, and proinsulin were predictive of diabetes, though to different degrees within each group. The mean chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 27 publications
1
70
2
1
Order By: Relevance
“…However, it has recently been reported that high proinsulin levels (which are reduced by metformin [24]) are pro-atherosclerotic in women, but not in men [25], and this might provide at least some explanation for our finding.…”
Section: Discussioncontrasting
confidence: 52%
“…However, it has recently been reported that high proinsulin levels (which are reduced by metformin [24]) are pro-atherosclerotic in women, but not in men [25], and this might provide at least some explanation for our finding.…”
Section: Discussioncontrasting
confidence: 52%
“…3,4 Lachin et al demonstrated that change in fasting glucose over the study duration was the strongest predictor of diabetes risk in the metformin and placebo arms, accounting for 14 % and 25 % of the decrease in risk over the course of the study in these two arms, respectively. 4 Among participants who had both impaired fasting glucose and impaired glucose tolerance at baseline, each standard deviation of mean weight loss was associated with a 34 % increased probability of regression to normal glucose regulation. 13 We now extend our understanding of these benefits by quantifying the predictive value of weight, glucose and HbA1c during the first 12 months of a preventive effort, and thereby inform approaches to intensifying preventive therapies in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Prior research in the DPP established that weight loss (more than physical activity) mediates the beneficial effects of lifestyle change, 3 and that both weight loss and reduced glycemia mediate the beneficial effects of metformin. 4 These analyses indicate the contribution of average weight loss over a 3-year period to the success of the trial's interventions. However, clinicians see their patients at high risk of diabetes at least yearly, if not more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…83 Some of the benefits of metformin were the result of weight loss rather than improvements in insulin sensitivity. 203 Lachin et al (2007) 203 estimated that 64% of the metformin benefit was mediated through weight loss. Interestingly, they note that the effect of weight loss achieved with metformin appears to be less than the same weight lost by lifestyle change.…”
mentioning
confidence: 99%